Experimental analysis of pre-compressed circular cylindrical shell under axial harmonic load. (September 2017) - Zippo, Antonio; Barbieri, Marco; Pellicano, Francesco
Abstract: In this paper the nonlinear dynamics of circular cylindrical shells under axial static (compressive) and periodic resonant loads have been experimentally investigated, the goal is to study the dynamic scenario and to analyze nonlinear regimes. A special test rig has been developed for the experiment in order to apply a static axial load combined with a dynamic axial load. The setup allows for investigating the linear behavior under static preload by means of the usual modal testing techniques; moreover, it allows for analyzing the nonlinear response which occurs when the dynamic axial load is periodic and gives rise to complex resonances. The complex dynamics, arising when a periodic axial load excites the asymmetric (shell like) modes, are analyzed by means of amplitude frequency diagrams, waterfall spectrum diagrams, bifurcation diagrams of Poincaré maps; a deep analysis of time histories, spectra, phase portraits and Poincaré maps completes the study of the complex dynamic scenario. Abstract : Highlights: The experimental setup is described. A technique for optimal open loop experiments is described. The role of pre-stress in widening instability regions is pointed out. The co-existence of different stable solutions (stationary, sub-harmonic, quasiperiodic, chaotic) is verified by experiments.